HUBUNGAN ANTARA KONTRASEPSI DMPA (DEPO MEDROXY PROGESTERON ASETAT) DENGAN PENINGKATAN BERAT BADAN AKSEPTOR KB DI PUSKESMAS PUNGGUR TAHUN 2018 - Weda Ayu Ardini (UNIVERSITAS HAJI SUMATERA UTARA, 2021)
The number of population in Indonesia is increasing, this is a big problem. Indonesia is the fifth country in the world with the highest estimated population of 249 million, with 2.6 Fertility or Total Fertility Rate (TFR) still high compared to other ASEAN countries with an average rate of 2.4 (Ministry of Health RI, 2014). Efforts to deal with the rate of Indonesian population hold a Family Planning program to achieve quality families, namely by regulating the number of children, while the most widely used contraceptives are DMPA injections, the most frequent side effect of DMPA injection contraception is weight gain which can result in drop out acceptors. The purpose of this study was to determine the relationship between DMPA (Depo Medroxy Progesteron Asetat) contraception and weight gain in KB acceptors at Punggur Health Center in 2018. The results of the research conducted by researchers on 133 respondents that there were 77 family planning acceptors (57.8%) using DMPA KB injections, and 73 acceptors (45.1%) KB acceptors at Purbolinggo Health Center experienced a one-year increase in weight after using the tool contraception. Based on the bivariate test of acceptors with DMPA injection contraception and weight gain of 43 (55.8%) KB acceptors. Based on the results of the chi-square analysis with a 95% confidence level obtained p-value = 0.004 <α (0.05), then Ha is accepted and Ho is rejected or means there is a relationship between DMPA injections with an increase in birth control weight gain in Punggur Health Center in 2018 and the Odds Ratio (OR) is 2.9. It is expected that health workers to improve family planning services, especially in the case of DMPA contraceptive use. And it is expected that KB acceptors will increase their knowledge, especially regarding contraceptives to be chosen so that they can minimize the effects of contraceptive device use and play a role in the national family planning program, namely Active KB acceptors.